2021
DOI: 10.1108/ijchm-05-2020-0477
|View full text |Cite
|
Sign up to set email alerts
|

The value proposition of food delivery apps from the perspective of theory of consumption value

Abstract: Purpose The theory of consumption values (TCV) has successfully explained much consumer choice behavior, but few studies have investigated the values that drive food-delivery application (FDA) use. This study aims to bridge this gap by extending the TCV to the FDA context to examine food consumption-related values and interpreting and rechristening generic consumption values to adapt the TCV to the FDA context. Design/methodology/approach An explorative mixed-method research approach was taken to conduct foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
1
29

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(238 citation statements)
references
References 113 publications
(169 reference statements)
10
161
1
29
Order By: Relevance
“…For example, Grubhub offers a $10-off promotion to new customers and a student discount ( Groupon, 2021 ). In OFD service setting, price saving promotions often serve as effective marketing tools as demonstrated by Kaur et al (2021) as well as Ray & Bala, 2021 who revealed that free delivery, lower delivery fees, or promotional incentives enhance CIU. Kaur et al (2021) further noted that customers using OFD services search for a price advantage.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Grubhub offers a $10-off promotion to new customers and a student discount ( Groupon, 2021 ). In OFD service setting, price saving promotions often serve as effective marketing tools as demonstrated by Kaur et al (2021) as well as Ray & Bala, 2021 who revealed that free delivery, lower delivery fees, or promotional incentives enhance CIU. Kaur et al (2021) further noted that customers using OFD services search for a price advantage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In OFD service setting, price saving promotions often serve as effective marketing tools as demonstrated by Kaur et al (2021) as well as Ray & Bala, 2021 who revealed that free delivery, lower delivery fees, or promotional incentives enhance CIU. Kaur et al (2021) further noted that customers using OFD services search for a price advantage. Thus, this study examines price saving benefits (PSB) as a critical predictor of CIU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some different theories explain the intention to use the FDA ( Kaur et al, 2021 , Lee, Sung, & Jeon, 2019 , Ray et al, 2019 , Song et al, 2021 ). However, according to previous studies and literature, the UTAUT is considered a critical and renowned theory ( Jadil et al, 2021 ) to explain the use of information systems and apps.…”
Section: Literature Reviewmentioning
confidence: 99%
“… ( Shan et al, 2020 ) The RANAS smartphone app-aided solution can resolve recycling behavioral improvements and can be used as an action-based training instrument to teach people about the environmental effects of recycling. From the viewpoint of consumption value theory, the value proposition of food delivery apps ( Kaur et al, 2020 ) For “Food Delivery App” service providers striving for larger market shares, the outcomes of the study are insightful by helping them understand how to affect customer choice and purchasing intentions. Assessment of the effect of smart phone technology on the balanced eating behavior and diet awareness of consumers ( Samoggia & Riedel, 2020 ) The recommendation is that customer behavior psychologists, marketing analysts, nutritionists, and software developers collaborate to create applications to increase the efficacy of nutrition awareness apps.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This study thus reflects on the linkage between MAP and SSP. Through a literature synthesis we have identified essential factors using the Theory of Consumption Values (TCV) ( Kaur et al, 2020 , Sheth et al, 1991 , Thongmak, 2020 ) and the Theory of Planned Behavior (TPB) ( Fishbein and Ajzen, 1975 , Sun et al, 2020 , Zaremohzzabieh et al, 2019 ) that influence MAP acceptance in the SSP. Therefore, the study examines how an SME owner should strategically handle the interdependencies between different entities, in order to create a sustainable mobile-app-based business during the pandemic and onwards ( Gomeseria, 2019 , Ho and Chung, 2020 ).…”
Section: Introductionmentioning
confidence: 99%